2013
DOI: 10.1002/gcc.22057
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of the ZC3H7B and BCOR genes in endometrial stromal sarcomas carrying an X;22‐translocation

Abstract: Endometrial stromal sarcomas (ESS) are genetically heterogeneous uterine tumors in which a JAZF1-SUZ12 chimeric gene resulting from the chromosomal translocation t(7;17)(p15;q21) as well as PHF1 rearrangements (in chromosomal band 6p21) with formation of JAZF1-PHF1, EPC1-PHF1, and MEAF6-PHF1 chimeras have been described. Here, we investigated two ESS characterized cytogenetically by the presence of a der(22)t(X;22)(p11;q13). Whole transcriptome sequencing one of the tumors identified a ZC3H7-BCOR chimeric tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
94
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 31 publications
3
94
0
Order By: Relevance
“…We, too, have in previous studies analyzed RNA-Seq data using the FusionMap program finding that it identified fusion genes that corresponded well with the available cytogenetic information and that were biologically significant [23], [24], [25], [26], [27], [28]. The present study, on the other hand, shows that although the same approach detected hundreds (FusionMap) or tens (FusionFinder) of fusion genes, the programs failed to detect the biologically important KAT6A-CREBBP fusion gene although it was manually retrievable from the raw sequencing data.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We, too, have in previous studies analyzed RNA-Seq data using the FusionMap program finding that it identified fusion genes that corresponded well with the available cytogenetic information and that were biologically significant [23], [24], [25], [26], [27], [28]. The present study, on the other hand, shows that although the same approach detected hundreds (FusionMap) or tens (FusionFinder) of fusion genes, the programs failed to detect the biologically important KAT6A-CREBBP fusion gene although it was manually retrievable from the raw sequencing data.…”
Section: Discussionmentioning
confidence: 94%
“…We and others have used combinations of cytogenetics and RNA-seq to detect the “primary” fusion genes of neoplasms carrying only one or a few chromosomal rearrangements. This approach was used to identify the WWTR1-CAMTA1 and YWHAE-FAM22A/B chimeric genes in epithelioid hemangioendothelioma and high-grade endometrial stromal sarcomas, respectively [21], [22], ZC3H7-BCOR in endometrial stromal sarcomas [23], IRF2BP2-CDX1 in a mesenchymal chondrosarcoma [24], and EWSR1-YY1 in a subset of mesotheliomas [25]. In hematologic malignancies, an NFIA-CBFA2T3 ( NFIA is located in 1p31) chimeric transcript was found in an acute erythroid leukemia with the translocation t(1;16)(p31;q24) [26], the ZMYND8-RELA fusion was detected in a congenital acute erythroid leukemia carrying a t(11;20)(p11;q13) translocation [27], and a cryptic FUS/ERG fusion gene was found in an acute myeloid leukemia with a rather complex karyotype [28].…”
Section: Introductionmentioning
confidence: 99%
“…The most common rearrangement, t(7;17)(p15;q21), results in JAZF1-SUZ12 gene fusion 59. Other gene fusions include JAZF1-PHF1 ( figure 2I ) , and the much less common EPC1-PHF1, MEAF6-PHF1 ,60 61 ZC3H7-BCOR 62 and MBTD1-CXorf67 63. Molecular testing, however, is not routinely performed but may be helpful when dealing with cases of unusual location or morphology.…”
Section: Low-grade Endometrial Stromal Sarcomamentioning
confidence: 99%
“…34 Two additional translocations have been described in ESSs, t(X;22) (p11;q13) and t(X ;17) (p11.2;q21.33) associated with a ZC3H7B-BCOR fusion and a MBTD1-CXorf67 fusion, respectively. 35,36 Although endometrial stromal tumors are genetically heterogeneous, the different genes involved in low-grade ESS are functionally related (PHF1, SUZ12, EPC1, MBTD1), being members of the polycomb gene family. Of interest, ZC3H7B-BCOR, MEAF6-PHF1, and EPC1-PHF1 fusions were also identified in ossifying fibromyxoid tumors and JAZ1-PFH1 in an ossifying sarcoma of the heart.…”
Section: Endometrial Stromal Sarcoma Low Gradementioning
confidence: 99%